ANALISIS PERILAKU MEMILIH PADA PEMILIHAN UMUM LEGISLATIF 2014 (Studi Kasus pada Masyarakat Kelurahan Kranggan, Semarang Tengah) - Ardi Ferdian; Hermini Susiatiningsih; Budi setiyono (Journal of Politic and Government Studies, 2015)
Election is one manifestation of democracy, where the principle of democracy itself is giving a voice to the people. Reality is happening in Indonesia is very much different, the results of the elections that have been held so far have not reaped considerable positive impact for the people. Indonesia is a country that is fairly consistent in holding elections, the electoral system used is proportional system, where the system is the number of seats obtained by a political party or group in accordance with the number of votes obtained from the public. Voting behavior of people in Indonesia can be categorized into several approaches, namely structural, sociological, ecological, social psychology, and rational choice. But the Indonesian people from voting as a psychological pride, such as fulfilling the obligation as citizens, confirms the identity of the group, and showed loyalty to the party. Most residents also use their voting rights based on the information that is incomplete and inaccurate, as tradition, ideology, and the image of the party. Voting behavior can be sized to describe how people make choices in elections and also can show how much the political participation of the people who do. Kelurahan Kranggan which became one of the region's economy in Semarang which cause the majority of the work was hailed by the people as a trader. In this Kranggan village also found the results of legislative elections in 2014 are unique, political party PDIP almost absolute win in this village. Based on this phenomenon the authors are interested in doing research on the behavior of selecting Kranggan community, and classify the types of voters in this Kranggan village. Research is carried out by distributing questionnaires to 100 respondents consisting of voters who have registered as voters for the legislative elections of 2014. The analysis technique used in this research is descriptive analysis, analysis and crosstab analysis frequencies.Keywords: Voting Behavior, legislative elections, political parties, candidates, Criteria, Political Participation.